2018
DOI: 10.1073/pnas.1720237115
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocyte cell death in the pea aphid/ Buchnera symbiotic system

Abstract: SignificanceBeneficial symbiotic associations, ubiquitously found in nature, have led to the emergence of eukaryotic cells, the bacteriocytes, specialized in harboring microbial partners. One of the most fundamental questions concerning these enigmatic cells is how organismal homeostasis controls their elimination. Here we report that aphid bacteriocytes have evolved a form of cell death distinct from the conserved cell-death mechanisms hitherto characterized. This cell-death mechanism is a nonapoptotic multis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 71 publications
6
76
0
Order By: Relevance
“…We showed that the relative abundance of B. aphidicola increased during the preadult stages; however, it declined throughout the adult lifespan. Our results are in congruence with a recent report that showed that Buchnera bacteriocytes increase significantly in number and size during the nymphal development of A. pisum (Simonet et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the relative abundance of B. aphidicola increased during the preadult stages; however, it declined throughout the adult lifespan. Our results are in congruence with a recent report that showed that Buchnera bacteriocytes increase significantly in number and size during the nymphal development of A. pisum (Simonet et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
“…In the pea aphid Acyrthosiphon pisum, the bacterium Buchnera provides specific amino acids that are lacking in the host's diet (Shigenobu et al 2000). Additionally, the bacterium only lives in specialized cells, the bacteriocytes, localized in the vicinity of the gut (Simonet et al 2018). In the most integrated associations, bacteria are concentrated in dedicated permanent organs, the bacteriomes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is able to co-opt host proteins to perform additional modifications on its own proteins, such as prenylation (e.g., farnesylation) (Al-Quadan et al 2011). Interestingly, interaction with the endoplasmic reticulum to form a replicative niche is common among pathogens, such as the alphaproteobacterium Brucella abortus and the Chlamydiales bacterium Simkania negevensis (Cornejo et al 2017) and is also altered in host-derived bacteriocytes that house mutualistic bacteria (Simonet et al 2018).…”
Section: E Post-translational Modification Of Host Genetic Regulatomentioning
confidence: 99%